2014
DOI: 10.1039/c4cc02749c
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic fused heterocyclic [22] macrocycles with NIR absorption

Abstract: Three related aromatic [22] heteroporphyrins have been synthesized and characterized, with the target of achieving NIR absorption. The propensity of these smallest π-conjugated macrocycles to absorb in the NIR region is benefitted from the fusion/annelation of the precursor heterocycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 33 publications
3
22
0
Order By: Relevance
“…With the insight from our recent observation, where fused ring expansion of the pyrrole moieties at the β positions and fused thiophene moieties resulted in NIR absorption, efforts were directed towards the synthesis of higher analogues (Scheme ) with free pyrrole moieties and fused thiophene moieties in order for the constructs to be rigidly planar and fully conjugated across the entirety of the porphyrinoid backbone. Based on our target macrocycles, the fused thieno [3, 2‐ b ] thiophene 1 has been synthesized following a literature report .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the insight from our recent observation, where fused ring expansion of the pyrrole moieties at the β positions and fused thiophene moieties resulted in NIR absorption, efforts were directed towards the synthesis of higher analogues (Scheme ) with free pyrrole moieties and fused thiophene moieties in order for the constructs to be rigidly planar and fully conjugated across the entirety of the porphyrinoid backbone. Based on our target macrocycles, the fused thieno [3, 2‐ b ] thiophene 1 has been synthesized following a literature report .…”
Section: Methodsmentioning
confidence: 99%
“…Column chromatographic separation over basic alumina, followed by repeated silica gel (200–400 mesh) chromatographic separation, yielded the macrocycles 6 and 7 in 5 and 6 % yields, respectively, as dark green solid. Acid concentration above one equivalent of trifluoroacetic acid led to acidolysis of the precursors 4 and 5 and yielded [22] heterocyclic macrocycles …”
Section: Methodsmentioning
confidence: 99%
“…Rath et al reported three heteroporphyrins 30–32 with built-in thienothiophene diol ( P28 ) and acenaphthylene/phenanthrene-annulated pyrrole ( P29 , P24 ) units (Scheme 6). 29 These thienothiophene-containing [22] heteroporphyrins absorb strongly in the NIR range. Annulated pyrroles in 31 and 32 contributed to π electron delocalization, red shifting their Soret band by 56 nm compared to 30 .…”
Section: Nir Absorbing Aromatic Expanded Porphyrinoids With Built-in Fused/annelated Heterocycle(s)mentioning
confidence: 99%
“…While the dihedral angles of the thieno[3,2‐ b ]thiophene segment toward the neighboring pyrrole units are relatively small (34.04–41.13°), the bond lengths of C( β )−C( β ) (1.411 and 1.396 Å) are as long as or longer than those of C( α )−C( β ) (1.395, 1.405, and 1.391 Å), implying a weak or negligible contribution of the thieno[3,2‐ b ]thiophene segments to the global macrocyclic conjugation. In contrast, a thieno[3,2‐ b ]thiophene involved in global π‐conjugation has been reported to display a characteristic bond length alternation such that the bond lengths of C( β )−C( β ) are apparently shorter than those of C( α )−C( β ) …”
Section: Figurementioning
confidence: 99%
“…In contrast, a thieno[3,2-b]thiophene involved in global p-conjugationh as been reported to display ac haracteristicb ond length alternation such that the bond lengths of C(b)ÀC(b)a re apparently shorter than those of C(a)ÀC(b). [12] The 1 HNMR spectrum of 3 shows as ymmetric pattern including three singlets at d = 9.38, 9.32, and 6.10 ppm due to the pyrrolic NH protons, ten doublets in the range of d = 8.45-5.29 ppm due to the pyrrolic b-protons, and four signals at d = 5. 95, 5.56, 4.37, and 4.21 ppm due to the bridging biphenyl segment, clearly suggesting the presence of ad iatropic ring current arising from the global 46p-electronic network (Figure S5-3).…”
mentioning
confidence: 98%